2017
DOI: 10.1038/s41598-017-16245-0
|View full text |Cite
|
Sign up to set email alerts
|

Sublethal effects of imidacloprid on targeting muscle and ribosomal protein related genes in the honey bee Apis mellifera L.

Abstract: A sublethal concentration of imidacloprid can cause chronic toxicity in bees and can impact the behavior of honey bees. The nectar- and water-collecting, and climbing abilities of bees are crucial to the survival of the bees and the execution of responsibilities in bee colonies. Besides behavioral impact, data on the molecular mechanisms underlying the toxicity of imidacloprid, especially by the way of RNA-seq at the transcriptomic level, are limited. We treated Apis mellifera L. with sublethal concentrations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
1
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 44 publications
2
34
1
3
Order By: Relevance
“…Regarding proteins related to the motor function of bees, it was observed that after eight days of contamination with sublethal concentrations of imidacloprid A. mellifera climbing ability was significantly reduced. Analyzes have shown that genes related to muscle function were downregulated, confirming the mobility impairment (Wu et al, 2017b). Motor alterations have also been reported in laboratory trials with sublethal doses of imidacloprid (Lunardi et al, 2017 andBovi et al, 2018).…”
Section: Imidaclopridmentioning
confidence: 58%
“…Regarding proteins related to the motor function of bees, it was observed that after eight days of contamination with sublethal concentrations of imidacloprid A. mellifera climbing ability was significantly reduced. Analyzes have shown that genes related to muscle function were downregulated, confirming the mobility impairment (Wu et al, 2017b). Motor alterations have also been reported in laboratory trials with sublethal doses of imidacloprid (Lunardi et al, 2017 andBovi et al, 2018).…”
Section: Imidaclopridmentioning
confidence: 58%
“…the mushroom bodies and antennal lobes; Barbara et al, 2008;Deglise et al, 2002;Palmer et al, 2013). It was recently found, however, that honeybees exposed to imidacloprid at 10 ppb showed significant down-regulation of muscle-related genes (Wu et al, 2017). This down-regulation, in addition to the blockage of nAChRs, may underlie the subtle motor deficits observed here and elsewhere.…”
Section: Discussionmentioning
confidence: 69%
“…IMI may remain on the water surface for a long time due to high water solubility [70]. IMI cannot be hydrolyzed by ACh esterase, causing interruption to nAChR leading to long-lasting effects, such as loss of reflexes, muscular weakness, and paralysis [71]. Consequently, it alters invertebrate movements and leads to starvation and death.…”
Section: Discussionmentioning
confidence: 99%